Stabilizing effect of TMAO on globular PNIPAM states: preferential attraction induces preferential hydration. Issue 46 (9th November 2016) - Schroer, Martin A.; Michalowsky, Julian; Fischer, Birgit; Smiatek, Jens; Grübel, Gerhard
Abstract : We study the effect of the organic co-solute trimethylamine N -oxide (TMAO) on the volume phase transition of microgel particles made from poly( N -isopropylacrylamide) (PNIPAM) using dynamic light scattering (DLS) and all-atom molecular dynamics (MD) simulations. Abstract : We study the effect of the organic co-solute trimethylamine N -oxide (TMAO) on the volume phase transition of microgel particles made from poly( N -isopropylacrylamide) (PNIPAM) using dynamic light scattering (DLS) and all-atom molecular dynamics (MD) simulations. The DLS measurements reveal a continuous TMAO-induced shrinking process from a coil to a globular state of PNIPAM microgel particles. Analyzing the DLS data by the phenomenological Flory–Rehner theory verifies the stabilization of the globular state of the particles in the presence of TMAO. Complementary atomistic MD simulations highlight a pronounced accumulation of TMAO molecules around PNIPAM chains. We observe a significant preferential attraction between TMAO and the globular state of PNIPAM, which is additionally stabilized by a larger number of hydrating water molecules compared to pure aqueous solutions. Further DLS measurements were also conducted on PNIPAM suspensions with the co-solute urea added. The observed differences compared with the results obtained for TMAO support the proposed mechanism.